Multi-attribute negotiation mechanism for manufacturing service allocation in smart manufacturing. (January 2022) - Kang, Kai; Qing Tan, Bing; Zhong, Ray Y.
Abstract: Smart manufacturing is undergoing rapid development along with many disruptive technologies, such as Internet of Things, cyber-physical system and cloud computing. A myriad of heterogeneous manufacturing services can be dynamically perceived, connected and interoperated to satisfy various customized demands. In smart manufacturing, the market equilibrium is variable over time due to changes in demand and supply. Thus, efficient manufacturing service allocation (MSA) is critical to implementation of smart manufacturing. This paper considers the MSA problem under market dynamics with maximization of utility of customers and service providers. Many conventional methods generally allocate manufacturing services to the customers by multi-objective optimization without considering the impact of interactions between customers and service providers. This paper presents a multi-attribute negotiation mechanism to address the MSA problem under time constraints relying on autonomous agents. The proposed negotiation mechanism is composed of two models: an atomic manufacturing service negotiation model and a composite manufacturing service coordination. The former model is based on automated negotiation to seek an atomic manufacturing service over multiple attributes for an individual subtask. The latter model incorporates the global distribution and surplus redistribution to coordinate and control multiple atomic manufacturing service negotiations for the whole manufacturing task. Numerical studies are employed to verify the effectiveness of the multi-attribute negotiation mechanism in solving the MSA problem. The results show that the proposed negotiation mechanism can address the MSA problem and surplus redistribution can effectively improve the success rate of negotiations.